A study of Taiwanese university students’ English use, learning goals and attitudes toward English as a lingua franca - Luo, Wen-Hsing (Studies in Second Language Learning and Teaching, 2018)
This study investigates Taiwanese university students’ experience of English use, aims of learning English and attitudes toward English as a lingua franca (ELF). The notion of ELF has been researched in the field of English language teaching. However, English teaching practice targeting native-speaker (NS) norms is still prevailing in English classrooms. To better respond to learner needs of using English in the age of globalization, this study explores learners’ English learning and use in relation to their attitudes toward ELF. Research methods including interviewing and questionnaire survey were employed to collect data from English majors at a university in Taiwan. The study finds that the learners were aware of the communicative value of ELF and actually used ELF in intercultural communication. The learners’ use of English in context affected their attitudes toward ELF and aims of learning English. It is found that the learners preferred English conforming to NS norms; yet, they wished to learn local variation of English concerning accents and word use. In light of the findings, the author suggests that English teachers incorporate an ELF perspective into English instruction and help learners develop intercultural awareness and competencies.